A New Concept of the Analytic Operator-Valued Feynman Integral on Wiener Space. (3rd April 2017) - Chang, Seung Jun; Skoug, David; Chung, Hyun Soo
ABSTRACT: In this article we introduce a new concept of an analytic operator-valued Feynman integral for functionals on Wiener space, which we then use to explain various physical phenomena. We then establish the existence of some analytic operator-valued Feynman integrals that prove useful in establishing various applications in quantum mechanics.